SURVEI MINAT DAN HASIL BELAJAR DALAM MENGIKUTI PEMBELAJARAN SEMASA NEW NORMAL COVID-19 PADA KELAS V SEKOLAH DASAR - Syofia alkhaira; Mai Sri Lena (Proyeksi: Jurnal Psikologi, 2021)
This study aims to describe student interest and learning outcomes in participating in learning during the new normal covid-19 in class V Elementary School Nagari Sei. Rotan, East Pariaman District, Pariaman City. The type of research is uses descriptive quantitative research with the survey method, the variables used is the single variables interest and student learning outcomes in participating in learning during the new normal covid-19 in class V Elementary School Nagari Sei. Rotan, East Pariaman District, Pariaman City. The data obtained were analyzed using Microsoft Eel and SPSS Windows 16, the analysis used was percentage descriptive analysis. The results showed that the interest and learning outcomes of students in participating in learning during the new normal covid-19 in class V Elementary School Nagari Sei. Rotan, East Pariaman District, Pariaman City was classified as good, namely 64.91% interest with very high categorization while for learning outcomes the value quite good, namely an average of 79.26% with a KKM value of 70. Interests are influenced by several indicators of interest such as feeling happy reaching the highest value, namely 21.12%, motivation 18.88%, expectations 18.61%, worth 18, 61%, feeling attracted 18.36%, needs 11.69%, lastly attention with a value of 11.32%. In this case the indicators that most influence interest and learning outcomes in following learning during the new normal covid-19 in class V Elementary School students Nagari Sei.Rotan, East Pariaman District, Pariaman City, namely feeling happy.